2022
DOI: 10.1021/acsmedchemlett.1c00549
|View full text |Cite
|
Sign up to set email alerts
|

Structure–Activity Relationship of Anti-Mycobacterium abscessus Piperidine-4-carboxamides, a New Class of NBTI DNA Gyrase Inhibitors

Abstract: Mycobacterium abscessus causes difficult-to-cure pulmonary infections. The bacterium is resistant to most anti-infective agents, including first line antituberculosis (anti-TB) drugs. MMV688844 (844) is a piperidine-4-carboxamide (P4C) with bactericidal properties against M. abscessus. We recently identified DNA gyrase as the molecular target of 844. Here, we present in silico docking and genetic evidence suggesting that P4Cs display a similar binding mode to DNA gyrase as gepotidacin. Gepotidacin is a member … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…[63][64][65][66][67] Additionally, we were interested in 2-((3R,4R)-3vinylpiperidin-4-yl)acetaldehyde, 8although this particular product is not commercially available, its Boc-protected derivative is used for stereocontrolled synthesis of drugs active against malaria parasites, including analogs of quinine and quinidine. [68][69][70][71] The computer-designed plans are detailed in Figure 5b, where 8, 10 and 12 share the first three synthetic steps: oxidation, condensation, and Beckmann fragmentation. Oxidation of quinine and condensation of the resulting ketone with hydroxylamine were previously described 72,73 , although the latter gave only moderate, 18% yield and could thus benefit from optimization of conditions.…”
Section: Degradation Of Quininementioning
confidence: 99%
See 1 more Smart Citation
“…[63][64][65][66][67] Additionally, we were interested in 2-((3R,4R)-3vinylpiperidin-4-yl)acetaldehyde, 8although this particular product is not commercially available, its Boc-protected derivative is used for stereocontrolled synthesis of drugs active against malaria parasites, including analogs of quinine and quinidine. [68][69][70][71] The computer-designed plans are detailed in Figure 5b, where 8, 10 and 12 share the first three synthetic steps: oxidation, condensation, and Beckmann fragmentation. Oxidation of quinine and condensation of the resulting ketone with hydroxylamine were previously described 72,73 , although the latter gave only moderate, 18% yield and could thus benefit from optimization of conditions.…”
Section: Degradation Of Quininementioning
confidence: 99%
“…In the case of amine 12 synthesis, our methodology (overall yield 44%) also appears advantageous to existing pathways, either the one including oxidative cleavage of ketone followed by N-tertbutoxycarbamate synthesis (with toxic diphenyl phosphoryl azide) and Curtius rearrangement (19%) 72,78 , or the second procedure starting from the previously mentioned toxic p-methoxyaniline 10 (13%). 68 Calculated production cost including solvents and reagents is estimated at 37.39 $/g, compared to the market price of 203 $/g.…”
Section: Degradation Of Quininementioning
confidence: 99%
“…[17a] Amide moieties of drug candidates are known to be hydrolyzed in blood plasma to form inactive metabolites. [19] The blood plasma of rodents typically exhibits higher and less specific hydrolase activity than human plasma due to differences in plasma esterases and their expression levels. [20] Both MMV and 2 were highly unstable during incubation with human and murine liver microsomes.…”
Section: Introductionmentioning
confidence: 99%
“…We have already presented plasma and microsomal stability data of the hit compound MMV and the highly active compound 2 and revealed that MMV degraded quickly in murine plasma, whereas 2 was stable in both murine and human plasma [17a] . Amide moieties of drug candidates are known to be hydrolyzed in blood plasma to form inactive metabolites [19] . The blood plasma of rodents typically exhibits higher and less specific hydrolase activity than human plasma due to differences in plasma esterases and their expression levels [20] …”
Section: Introductionmentioning
confidence: 99%